Characterization of bacterial endophytes from the roots of native and cultivated Brazil nut trees (Bertholletia excelsa) - Patrícia Bombonati CHALITA; Eliane do Nascimento Cunha FARIAS; Ismaele Breckenfeld da COSTA; Brenda Ferreira SOUSA; Marco Antônio Oliveira dos SANTOS; Teresinha Costa Silveira de ALBUQUERQUE; Marcos José Salgado VITAL; Krisle da SILVA (Acta Amazonica, 2019)
ABSTRACT Brazil nut is a very important nontimber forest product in the Amazon region. Propagation of this tree still represents a challenge due to slow and uneven seed germination. In this context, plant growth-promoting bacteria can facilitate the process of propagation. The aims of this study were to isolate and characterize endophytic bacteria from the roots of Brazil nut trees in native terra firme forest and cultivation areas in northern Brazil, and to identify mechanisms by which bacteria act in plant growth promotion. Overall, 90 bacterial isolates were obtained from the roots of Brazil nut trees in monoculture, agroforestry and native forest areas by using different semisolid media. The isolates were characterized by sequencing the 16S rRNA gene. Plant growth-promoting characteristics were evaluated by the presence of the nifH gene, aluminum phosphate solubilization and the production of indole compounds. The isolates were affiliated with 18 genera belonging to 5 different classes (α-Proteobacteria, β-Proteobacteria, γ-Proteobacteria, Bacilli and Actinobacteria). The genus Bacillus was predominant in the forest and monoculture areas. Fourteen isolates presented the nifH gene. Most of the bacteria were able to solubilize aluminum phosphate and synthetize indole compounds. The results indicated high diversity of endophytic bacteria present among the roots of Brazil nut trees, mainly in the agroforestry area, which could be related to soil attributes. Among the 90 isolates, the 22 that presented the best results regarding plant growth promotion traits were good candidates for testing in seedling production of Brazil nut trees.